Comment on ‘A solution of the bosonic and algebraic Hamiltonians by using an AIM’ - Fernández, Francisco Marcelo (2011)
We analyze a recently proposed variant of the asymptotic iteration method for bosonic Hamiltonians (Koç et al 2010 J. Phys. A: Math. Theor. 43 395208). We show that the main equations proposed by the authors are inconsistent and only apply to trivial problems. We conjecture how the authors obtained their results for nontrivial models.